2023
DOI: 10.1126/science.adf2678
|View full text |Cite
|
Sign up to set email alerts
|

A luminous fast radio burst that probes the Universe at redshift 1

S. D. Ryder,
K. W. Bannister,
S. Bhandari
et al.

Abstract: Fast radio bursts (FRBs) are millisecond-duration pulses of radio emission originating from extragalactic distances. Radio dispersion is imparted on each burst by intervening plasma, mostly located in the intergalactic medium. In this work, we observe the burst FRB 20220610A and localize it to a morphologically complex host galaxy system at redshift 1.016 ± 0.002. The burst redshift and dispersion measure are consistent with passage through a substantial column of plasma in the intergalactic medium and extend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 98 publications
3
26
0
Order By: Relevance
“…), which will achieve subarcsecond localizations of FRBs beginning in early 2024 thanks to the addition of outrigger telescopes to the array, will significantly increase the rate of well-localized low-DM events. Above z  0.1, where the typical ULX flux scaling drops below the Chandra sensitivity threshold (see Figure 4), and as FRB experiments increase their horizon beyond the current z ∼ 1 (Ryder et al 2023), it will be possible with next-generation X-ray observatories, such as NewAthena and the Advanced X-ray Imaging Satellite (AXIS), to perform productive searches for ULX-like counterparts.…”
Section: Searching For X-ray Counterpartsmentioning
confidence: 99%
See 1 more Smart Citation
“…), which will achieve subarcsecond localizations of FRBs beginning in early 2024 thanks to the addition of outrigger telescopes to the array, will significantly increase the rate of well-localized low-DM events. Above z  0.1, where the typical ULX flux scaling drops below the Chandra sensitivity threshold (see Figure 4), and as FRB experiments increase their horizon beyond the current z ∼ 1 (Ryder et al 2023), it will be possible with next-generation X-ray observatories, such as NewAthena and the Advanced X-ray Imaging Satellite (AXIS), to perform productive searches for ULX-like counterparts.…”
Section: Searching For X-ray Counterpartsmentioning
confidence: 99%
“…Technical upgrades to a number of FRB experiments in recent years have facilitated a small, but growing number of (sub)arcsecond localizations and robust host galaxy identifications for approximately three dozen events (e.g., Bhardwaj et al 2021;Kirsten et al 2022;Gordon et al 2023;Law et al 2023;Ravi et al 2023;Ryder et al 2023;Sharma et al 2023). The first population studies demonstrate that FRB hosts span a wide range of stellar masses and star formation rates (SFRs) and trace the underlying population of field galaxies (Heintz et al 2020;Bhandari et al 2022;Gordon et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The low burst yield per source poses challenges in detecting potential periodicity in burst emissions or confidently ruling out its existence. Moreover, recent evidence suggests the existence of an energetic burst population at high redshifts (Ryder et al 2023), emphasizing the significance of enhancing detection yield to effectively employ them as cosmological probes (Macquart et al 2020). To comprehensively characterize the luminosity distribution of FRBs, it becomes imperative to detect and analyze bursts that lie near or below the detection thresholds of current instruments that may have been missed due to the incompleteness of existing search techniques.…”
Section: Introductionmentioning
confidence: 99%
“…If placed at z > 1 or behind another magnitude of extinction, the identification of the host would become prohibitively expensive for even the largest ground-based telescopes. FRB hosts have been found at z ∼ 1 (Ryder et al 2023), while Marnoch et al (2023) presented follow-up of FRB 20210912A, which is still without an identified host despite deep observations with the Very Large Telescope-even deeper optical time is required for these high-redshift FRBs through limited telescope resources. Another scenario is an FRB localized at low Galactic latitude, where dust extinction from the Galactic plane hampers optical follow-up.…”
Section: Introductionmentioning
confidence: 99%